Acute respiratory distress syndrome after convalescent plasma use: treatment of a patient with Ebola virus disease contracted in Madrid, Spain. Issue 7 (July 2015) - Mora-Rillo, Marta; Arsuaga, Marta; Ramírez-Olivencia, Germán; de la Calle, Fernando; Borobia, Alberto M; Sánchez-Seco, Paz; Lago, Mar; Figueira, Juan C; Fernández-Puntero, Belén; Viejo, Aurora; Negredo, Anabel; Nuñez, Concepción; et al.
Summary Background In the current epidemic of Ebola virus disease, health-care workers have been transferred to Europe and the USA for optimised supportive care and experimental treatments. We describe the clinical course of the first case of Ebola virus disease contracted outside of Africa, in Madrid, Spain. Methods Herein we report clinical, laboratory, and virological findings of the treatment of a female nurse assistant aged 44 years who was infected with Ebola virus around Sept 25–26, 2014, while caring for a Spanish missionary with confirmed Ebola virus disease who had been medically evacuated from Sierra Leone to La Paz-Carlos III University Hospital, Madrid. We also describe the use of experimental treatments for Ebola virus disease in this patient. Findings The patient was symptomatic for 1 week before first hospital admission on Oct 6, 2014. We used supportive treatment with intravenous fluids, broad-spectrum antibiotics, and experimental treatments with convalescent plasma from two survivors of Ebola virus disease and high-dose favipiravir. On day 10 of illness, she had acute respiratory distress syndrome, possibly caused by transfusion-related acute lung injury, which was managed without mechanical ventilation. Discharge was delayed because of the detection of viral RNA in several bodily fluids despite clearance of viraemia. The patient was discharged on day 34 of illness. At the time of discharge, the patient had possible subacute post-viral thyroiditis. None of the people who had contact with the patient before and after admission became infected with Ebola virus. Interpretation This report emphasises the uncertainties about the efficacy of experimental treatments for Ebola virus disease. Clinicians should be aware of the possibility of transfusion-related acute lung injury when using convalescent plasma for the treatment of Ebola virus disease. Funding La Paz-Carlos III University Hospital.